Rompslomp en Soutstories (Helter-Skelter and Salty Yarns) : Creating place for meaning in a forgotten bay - Kellerman, Beatrix (School of Architecture, Planning and Geomatics, 2014)
This dissertation examines the creation of public place that is rich in experience. The design project is located at the Small Fishing Harbour of Saldanha Bay. The research was based primarily on the following: Topics around place character and meaning were investigated and the use of poetry as a phenomenological method to illuminate the character of place was researched. The significance of recovered landscapes and peripheral sites was also investigated. The possibility of uncovering different spatial identities of site by investigating space at different scales was researched. New technologies that are suitable for application in the specific context such as fog catchers and Integrated Multi-trophic Aquaculture (IMTA) practices were also investigated. Through theoretical research the conclusion was reached that it is important to create place in such a way that it is rich in experience and has unique character. Places that are rich in experience have the potential to carry meaning in the minds of their users. Place needs both character and meaning for people to be able to identify with it and have a sense of belonging. Urban analysis showed that the Small Fishing Harbour is a peripheral site which is very important in terms of its physical location in the town of Saldanha Bay. It provides access to the water's edge to a segregated community. It was concluded that re (claiming) the Small Fishing Harbour as public place, through remediation of the site and an improved urban link to the town centre, is necessary for it to become a sustainable public place. It was illustrated that understanding existing context in terms of history and different spatial identities is important. Site specifics inform how existing experiences can be celebrated and/or reinforced in the design project.